2018
DOI: 10.19080/ijesnr.2018.15.555923
|View full text |Cite
|
Sign up to set email alerts
|

Soil Erosion Modeling Using GIS Based RUSEL Model in Gilgel Gibe-1 Catchment, South West Ethiopia

Abstract: Materials and Methods Description of the study areaGilgel Gibe-1 catchment is located in South West part of Ethiopia in Jimma zone of Oromia Regional State in Omo-Ghibe basin with a total area of 4218 km 2 at the dam site(outlet) and it is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The smallest class was settlement/ built-up area. A study conducted in Gigel Gibe-I catchment (central part of Omo-Gibe) also found the same trends of LULC (Gizaw and Degifie, 2018). The OA (86.94%) and K statistical test (0.8) conducted using 521 sampled reference observations has been found within the range of the acceptable limits (Anderson et al 1976) (Table 3).…”
Section: Cover and Management (C-value)mentioning
confidence: 52%
See 4 more Smart Citations
“…The smallest class was settlement/ built-up area. A study conducted in Gigel Gibe-I catchment (central part of Omo-Gibe) also found the same trends of LULC (Gizaw and Degifie, 2018). The OA (86.94%) and K statistical test (0.8) conducted using 521 sampled reference observations has been found within the range of the acceptable limits (Anderson et al 1976) (Table 3).…”
Section: Cover and Management (C-value)mentioning
confidence: 52%
“…Where by, P is the mean annual rainfall in mm generated from 30 years (1999-2018) rainfall data collected from Ethiopian National Meteorological Agency. Inverse Distance weighted (IDW) method was then implemented to generate the rainfall erosivity (R) value across the river basin and R-factor map was generated as a raster layer (Gizaw and Degifie, 2018).…”
Section: Rainfall-runoff Erosivity Factor (R)mentioning
confidence: 99%
See 3 more Smart Citations